Numerical investigations of hydraulic transient and thermodynamic characteristics of water flow impacting air pocket inside pipe based on CLSVOF. Issue 4 (14th June 2022) - Zhu, Jianghui; Duan, Xiangyu; Wu, Guohong; Li, Xiaoqin; Tang, Xuelin
Abstract: The hydraulic transient and thermodynamic characteristics of water flows impacting an air pocket at the vertical end of an elbow pipe are investigated. The CLSVOF (coupled level-set and volume of fluid) and URANS (unsteady Reynolds-averaged Navier–Stokes) equations with energy equation are implemented, where the RNG (Re-Normalization Group) k – ε turbulence model is adopted and the pressure–density equation is introduced to allow for the water-phase compressibility. All numerical predictions are consistent with the experimental in the literature. The evolution characteristics and mechanism of the water–air interface are analyzed based on the Froude number and dimensionless water–air mixing degree. For air-pocket Type I and Type II with the water–air mixing degree threshold of 10%, based on the first law of engineering thermodynamics and related process laws and basic theory of statistics, the applicability of the ideal gas model in the thermodynamic process of air pocket, the polytropic index regulation in the evolution process and its association with relevant typical thermodynamic processes are systematically analyzed. The polytropic index of air-pocket Type I fluctuates a little with the averaged median of 1.35 in different transient periods under different initial pressure conditions, while it fluctuates largely with the averaged median of 1.26 and 1.21 under the low and the high initial pressure conditions, respectively. HIGHLIGHTS: The CLSVOF model can better capture the pressure peak and water–air interface fragments than the VOF model. The thermodynamic process was close to adiabatic for air-pocket Type I and close to a compromised one between adiabatic and isothermal for air-pocket Type II. The recommended polytropic indexes were 1.32 for low initial pressure conditions and 1.29 for high initial pressure conditions. Graphical Abstract